Diversity and Genomic Characterization of a Novel Parvarchaeota Family in Acid Mine Drainage Sediments - Luo, Zhen-Hao; Li, Qi; Lai, Yan; Chen, Hao; Liao, Bin; Huang, Li-nan (Frontiers in Microbiology, 2020)
Recent genome-resolved metagenomic analyses of microbial communities from diverse environments have led to the discovery of many novel lineages that significantly expand the phylogenetic breadth of Archaea. Here, we report the genomic characterization of a new archaeal family based on five metagenome-assembled genomes retrieved from acid mine drainage sediments. Phylogenomic analyses placed these uncultivated archaea at the root of the candidate phylum Parvarchaeota, which expand this lesser-known phylum into two family levels. Genes involved in environmental adaptation and carbohydrate and protein utilization were identified in the ultra-small genomes (estimated size 0.53–0.76 Mb), indicating a survival strategy in this harsh environment (low pH and high heavy metal content). The detection of genes with homology to sulfocyanin suggested a potential involvement in iron cycling. Nevertheless, the absence of the ability to synthesize amino acids and nucleotides implies that these archaea may acquire these biomolecules from the environment or other community members. Applying evolutionary history analysis to Parvarchaeota suggested that members of the two families could broaden their niches by acquiring the potentials of utilizing different substrates. This study expands our knowledge of the diversity, metabolic capacity, and evolutionary history of the Parvarchaeota.